The Effect of Institutional Ownership and Investment Decisions on Manufacturing Company Value in Indonesia Stock Exchange - Joseph P. Kambey; Rusel Mangintiku (AIBPM Publisher, 2018)
The purpose of this study was to determine the effect of institutional ownership and investment decisions on company value. This study was conducted at a manufacturing company listed on the Indonesian stock exchange in the index LQ-45 in 2012 -2016. Purposive sampling was used as an election method with 3 criteria that produced 9 companies as samples that were worth observing Eviews 9. The data analysis employed panel data regression analysis with the use of model estimation of fixed effect model. The results showed that institutional decisions affect negatively the company value while investment decisions do not affect the company value. Keywords: company value, institutional ownership, investment decision